Manajemen pengetahuan dan kinerja organisasi: Peran mediasi inovasi dan motivasi - Zelsa Yorinda Kurniawati; Cepi Safruddin Abdul Jabar (Curricula: Journal of Curriculum Development, 2026)
Education in Indonesia faces significant challenges in improving organizational performance, as reflected in the 2023 PISA results showing that Indonesian students scored below international averages in literacy, mathematics, and science. Effective knowledge management is therefore a strategic solution. This study aims to examine the effect of knowledge management on organizational performance mediated by innovation and motivation. This study employed a cross-sectional quantitative design conducted in public elementary schools in Kalasan District, Yogyakarta. A total of 82 respondents were selected from schools with a minimum of two classes. Data were collected through questionnaires distributed to principals, teachers, and educational staff, and analyzed using PLS-SEM. Instrument validity and reliability were assessed using Average Variance Extracted and Cronbach's Alpha. Results indicate that knowledge management significantly and positively affects organizational performance, innovation, and motivation. Innovation positively influences organizational performance and successfully mediates the relationship between knowledge management and organizational performance. Conversely, motivation neither affects organizational performance nor mediates that relationship. Elementary schools should develop knowledge management systems that foster instructional innovation as a core strategy for improving educational quality.